SELECTED ASPECTS OF ALLO- AND XENOGRAFT MODEL APPLICATIONS FOR DEVELOPING NOVEL ANTI-CANCER VACCINES AND ONCOLYTIC VIRUSES - T. S. Nepomnyashchikh; E. V. Gavrilova; R. A. Maksyutov (Медицинская иммунология, 2019)
To date, cancer diseases are one of the leading causes of mortality and morbidity in the world. Recent advances in understanding the molecular genetic mechanisms of oncogenesis and anti-cancer immune responses open new opportunities for the development of novel effective therapeutic strategies against cancer diseases; the strategies that would be more specific to tumor cells and less toxic to the host. Immunotherapeutic anti-cancer vaccines and oncolytic viruses are among the most promising approaches of this kind. For rapid and reliable screening and preclinical testing of new therapeutic approaches the relevant animal models are of critical importance. Such models provide the ability to partially reproduce tumor microenvironment and vascularization, as well as to reproduce at some extent the immune system reactions. Allograft and xenograft tumor models are the most common in cancer research. Allogenic transplantation involves the cancer cells or tumor fragments transfer between the organisms of the same species. Xenoplastic transplantation involves the transfer of tumor cells or tissues between the organisms of distinct species. Both tumor cell lines and patient-derived tumor cells and fragments obtained with biopsy can be used for xenotransplantation. Over the past decades the researchers developed numerous strains of immunodeficient mice and rats, suitable for xenografting human tumors. However, despite the widespread of immunodeficient laboratory animals as in vivo models in experimental oncology, these models do also have significant limitations associated with inability to fairly reproduce the tumor microenvironment and human immune system functions in mice, and also with the development of graft versus host reactions. Thus, when planning the experiments, it is necessary to carefully analyze all the advantages and disadvantages of animal strains, supposed to be used in experimental oncology studies.